L’agriculture durable au Vietnam : une étude de cas dans le delta du Mékong - Louis Tanguay; Rodolphe De Koninck (VertigO, 2014)
Beginning in the mid-1980s, in the context of a genuine green revolution, Vietnamese agriculture underwent major transformations. In several regions, traditional crops gave way to intensive rice monoculture, a trend favoured by reforms associated with Doi Moi. This generated a number of problems, in the face of which new government policies were adopted favouring in turn more sustainable agricultural systems. Through case studies carried out in two Mekong delta communes, we examine two integrated agriculture-aquaculture systems promoted by the government’s support programme for sustainable agriculture and conclude that these systems can to some degree reach both the government’s goals and adhere to the principles of sustainable agriculture.